Simulated impact response of a 3-D printed skull, with an ellipsoidal excision, using finite element analysis - Gibson, Michael C.; Franceskides, Constantinos; Zioupos, Peter (European Society of Biomechanics, 2016)
This paper investigates methods of determining the influence of an ellipsoidal excision (14.2x11.8 mm occipital region) on the structural integrity of a human skull when exposed to impact loading. Experimental and simulation-based analyses were conducted, using 3-D printed replicas and a finite element model; both were derived from a clinical CT scan of the patient (28 YO MC, with no previous health concerns). Previous simulation studies [1] have achieved managed to predict skull fracture locations effectively for nonexcised skulls.